Pengembangan Sistem Informasi Roadbook untuk Program Tur Perjalanan Wisata Berbasis Web dengan Metode RUP (Rational Unified Process) Pada PT. Quest Travel Indonesia - I Gede Wiwekananda; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Quest Travel Indonesia is a travel agency company in Indonesia for French tourists. During the operational practices, problems arise when recording tour program bookings which is recapitulated become roadbook report. The operational process that takes days and often occurs of human error. Besides that, the problems on the process of monitoring tour that rely communication by phone and documentation of monitoring are not really definite. Based on these problems, a roadbook information system web-based using the RUP (Rational Unified Process) to help fix the company's business process. By implementing the RUP, the problem solving process can be done well because the iteration process repeats on the stages from the beginning to the end of the system development that could minimize errors in the system while being developed. The result of this study is a roadbook information system tour travel program web-based that has 34 features consisting of 79 functional and 3 non functional requirement. This system passes 3 tests with the black-box testing method that produces valid values ​​on all test items, compatibility testing which results in a number of major and minor issues on several browser, and User Acceptance Testing (UAT) which get final score of 93.3% or strongly agree. Based on the test results, it can be concluded that the roadbook information system for tour travel programs can improve and support business processes including ease in managing order data recording, monitoring tour travel, and making roadbook reports.